2019
DOI: 10.1371/journal.pone.0218635
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variability of sleep and nocturnal cardiac autonomic activity in elite female soccer players during an international tournament

Abstract: PurposeTo describe individual sleeping patterns and nocturnal cardiac autonomic activity of National team female soccer players during an international tournament.Materials and methodsTwenty elite female soccer players (aged 25.2±3.1 years) wore wrist actigraph units and heart rate (HR) monitors during night-sleep throughout 9 consecutive days (6 day-time training sessions [DT], 2 day-time matches [DM], and 1 evening-time match [EM]) of an international tournament. Training and match loads were monitored using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 70 publications
5
36
1
Order By: Relevance
“…In the current study, no significant changes in HRV indices across the 5-day tournament and an unclear within-subject correlation with s-RPE were observed. Our finding is in line with the results described in elite female national soccer players [ 20 ]. Other studies also reported that the fitter young soccer players with greater exercise tolerance had lower daily allostatic perturbation, leading to smaller daily changes in lnRMSSD, and in turn, lower CV values, as well as reduced perceived fatigue [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, no significant changes in HRV indices across the 5-day tournament and an unclear within-subject correlation with s-RPE were observed. Our finding is in line with the results described in elite female national soccer players [ 20 ]. Other studies also reported that the fitter young soccer players with greater exercise tolerance had lower daily allostatic perturbation, leading to smaller daily changes in lnRMSSD, and in turn, lower CV values, as well as reduced perceived fatigue [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Accelerometer data were extracted using the Sadeh’s (S) algorithm—originally validated on a healthy sample of adolescents and young adults (age range 10–25 years) [ 28 ]. Sleep outcomes included sleep duration (amount of sleep hours) and sleep efficiency (percentage of time in bed that was spent asleep) [ 20 , 28 ] were analyzed according to the National Sleep Foundation guidelines [ 2 ]. A sleep duration <8 h was considered an indicator of inappropriate sleep quantity, and a sleep efficiency ≤74% was considered an inappropriate sleep quality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular fitness is one of the most important aspects of physical fitness in soccer (Castagna et al, 2017;Slimani and Nikolaidis, 2019). During professional competitions, athletes dispute between two and five games per month, with each game lasting for ∼90 min, a time span, that, in case of a tie, can be extended (Castagna et al, 2010;Costa et al, 2019). Moreover, athletes have training sessions twice a day during the competitive season and take part in national and international championships (Slimani et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%